Comparison Between Fuzzy, Neuro-Fuzzy and Neural Network Models To Estimate the Expansion of Coffee Berry Borer in Colombian Coffee Crops - Bazurto, Nychol; Martínez, Carlos; Espitia, Helbert (TECCIENCIA, 2017)
In this paper we carry out a comparison among different techniques applied to simulation and representation of the expansion of the coffee berry borer in the Colombian coffee crops. First, we make a brief description of techniques: neural networks, neuro-fuzzy and fuzzy logic. Then, the models implementation is described and finally, we shown the comparison among these models, highlighting performance of neural networks.